BUSCHKE-LOWENSTEIN TUMOR PREGNANCY (CLINICAL CASE) - Татьяна Владимировна Ананьева; Ирина Николаевна Климчук; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Кира Борисовна Мозес; Елена Владимировна Рудаева; Кристина Владимировна Марочко; Карина Андреевна Васильева; Ангелина Александровна Гришина (Медицина в Кузбассе)
Buschke-Lowenstein tumor (OBL) or giant acumineal wart, most commonly caused by human papillomavirus types 6 and/or 11, 16 and 18, sexually transmitted, rare, the frequency of which is estimated at 0.1 % of the general population. OBL occurs more often in men than in women with a predominance of men, in a ratio of 3.5 : 1 with women. Most often under the age of 50 years and rarely occurs in children.